Conditionally reprogrammed cells (CRC) methodology does not allow the in vitro expansion of patient‐derived primary and metastatic lung cancer cells. Issue 1 (26th January 2018) - Sette, Giovanni; Salvati, Valentina; Giordani, Ilenia; Pilozzi, Emanuela; Quacquarini, Denise; Duranti, Enrico; De Nicola, Francesca; Pallocca, Matteo; Fanciulli, Maurizio; Falchi, Mario; Pallini, Roberto; De Maria, Ruggero; et al.
Abstract : Availability of tumor and non‐tumor patient‐derived models would promote the development of more effective therapeutics for non‐small cell lung cancer (NSCLC). Recently, conditionally reprogrammed cells (CRC) methodology demonstrated exceptional potential for the expansion of epithelial cells from patient tissues. However, the possibility to expand patient‐derived lung cancer cells using CRC protocols is controversial. Here, we used CRC approach to expand cells from non‐tumoral and tumor biopsies of patients with primary or metastatic NSCLC as well as pulmonary metastases of colorectal or breast cancers. CRC cultures were obtained from both tumor and non‐malignant tissues with extraordinary high efficiency. Tumor cells were tracked in vitro through tumorigenicity assay, monitoring of tumor‐specific genetic alterations and marker expression. Cultures were composed of EpCAM+ lung epithelial cells lacking tumorigenic potential. NSCLC biopsies‐derived cultures rapidly lost patient‐specific genetic mutations or tumor antigens. Similarly, pulmonary metastases of colon or breast cancer generated CRC cultures of lung epithelial cells. All CRC cultures examined displayed epithelial lung stem cell phenotype and function. In contrast, brain metastatic lung cancer biopsies failed to generate CRC cultures. In conclusion, patient‐derived primary and metastatic lung cancer cells were negatively selected under CRC conditions, limiting the expansion to non‐malignant lung epithelial stem cells from either tumor or non‐tumor tissue sources. Thus, CRC approach cannot be applied for direct therapeutic testing of patient lung tumor cells, as the tumor‐derived CRC cultures are composed of (non‐tumoral) airway basal cells. Abstract : What's new? Availability of matched tumor and non‐tumor patient‐derived models would promote the development of more effective therapeutics for non‐small cell lung cancer (NSCLC). The conditionally reprogrammed cells (CRC) methodology recently demonstrated exceptional potential, but controversy remains regarding the possibility to obtain tumor cell cultures under CRC conditions. Here, patient‐derived primary and metastatic lung cancer cells were negatively selected under CRC conditions, limiting the expansion to non‐malignant lung epithelial stem cells either from tumor or non‐tumor tissue sources. Thus, the CRC approach cannot be exploited for lung cancer therapeutic testing, as established CRC cultures are composed exclusively of (non‐tumoral) airway basal cells.